Analisis Pengelolaan Dana Non-Halal Bank Syariah Indonesia - Syam, Andi Hunafah Balqis; Widyananto, Arief (LPPM Universitas Islam 45, 2024)
Islamic banks are financial institutions that operate according to sharia, the existence of non-halal funds in Islamic banks is something that is still not widely known by the public which then creates misperceptions that Islamic banks accept non-halal funds as being considered the same as conventional banks. This research aims to provide literacy to readers that the management of funds from non-halal activities received at Indonesian Sharia Banks is not the same as conventional banks by carrying out a descriptive qualitative approach, namely conducting interviews with sources regarding non-halal funds at Islamic Banks. From the results of the analysis that has been carried out by the author, Bank Syariah Indonesia receives non-halal funds from activities carried out with fellow partners such as bonds or contract defects due to the customer's negligence in maintaining the trust that has been given by Bank Syariah Indonesia. The non-halal funds obtained are then separated from operational income funds because this income is not allowed to be considered as income in accordance with the DSN MUI fatwa. Funds which are then not considered as Bank Syariah Indonesia income funds will be channeled back to the community for public purposes such as public facilities referring to the enacted laws and Islamic law.